Nutrition for Healthy Skin Strategies for Clinical and Cosmetic Practice - Krutmann, Jean; Humbert, Philippe (Springer Berlin Heidelberg : Imprint: Springer, 2011)
During the past few years, significant scientific evidence has accumulated to show that nutrition-based strategies are capable of exerting beneficial effects on the skin. This exceptional reference • describes the scientific basis for nutrition-based strategies, • summarizes the evidence that functional food for skin really works, and • addresses key practical issues regarding the use of nutrition-based strategies in clinical and cosmetic dermatology. It is anticipated that this helpful guide, written by acclaimed international experts, will become the gold standard on the role of nutrition in ensuring healthy skin. It will be of interest to a wide audience, including dermatologists, food industry staff, patients, and consumers.